2014
DOI: 10.5116/ijme.531a.f2c9
|View full text |Cite
|
Sign up to set email alerts
|

Night shifts, sleep deprivation, and attention performance in medical students

Abstract: ObjectivesTo determine attention performance of medical students after sleep deprivation due to night shift work.MethodsProspective cohort design. All seventh, eighth and ninth semester students were invited to participate (n= 209). The effectiveness and concentration indices (d2 Test for attention, dependent variable) from 180 students at 3 evaluations during the semester were compared. Eighth and ninth semester students underwent their second evaluation after a night shift. The independent variables were noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
1
19
1
6
Order By: Relevance
“…Such studies often have a narrow focus on disease states, limiting their ability to provide a holistic assessment of physical, emotional and cognitive wellbeing [4–6]. The importance of physical and cognitive function is especially appreciable in the student population, 52% of whom play sport at least once a week.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies often have a narrow focus on disease states, limiting their ability to provide a holistic assessment of physical, emotional and cognitive wellbeing [4–6]. The importance of physical and cognitive function is especially appreciable in the student population, 52% of whom play sport at least once a week.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have investigated the effects of acute sleep deprivation, few focus on university students, despite the prevalence and impact of sleep deprivation in this population [4,5]. Such studies often have a narrow focus on disease states, limiting their ability to provide a holistic assessment of physical, emotional and cognitive wellbeing [4][5][6].…”
mentioning
confidence: 99%
“…Such studies often have a narrow focus on disease states, limiting their ability to provide a holistic assessment of physical, emotional and cognitive wellbeing [4][5][6]. The importance of physical and cognitive function is especially appreciable in the student population, 52% of whom play sport at least once a week.…”
mentioning
confidence: 99%
“…[5][6][7] Other studies have examined the effect of sleep deprivation on doctors by means of questionnaire such as the d2 test and the continuous performance test, showing altered attention and working memory. 8 From the perspective of the impact observed on the mental health and emotions of medical residents after 24 hours on call shifts, several studies have found negative effects of sleep deprivation on variables such as burn out, perceived stress and anxiety. 9,10 Sleep disturbances also affect the emotional state or mood of the subject.…”
Section: Introductionmentioning
confidence: 99%